Penyusunan bahan ajar Sastra Makassar bagi Guru Bahasa Daerah di Kabupaten Takalar - Syamsudduha Syamsudduha; Kembong Daeng; Sakinah Fitri; Hajrah Hajrah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this activity is to improve the qualityof local language learning. Therefore, the quality of locallanguage teachers must be continuously improved, both interms of curriculum implementation, preparation of learningmedia, mastering local language materials, implementinglanguage learning models, and learning assessment systems. Inthis program, several stages were carried out, namely (1)preparation: opening and distributing pre-tests and trainingcontracts; (2) presentation of materials; (3) practice andsimulation; (4) mentoring; (5) evaluation. This program wascarried out with a number of partners including the Head ofEducation, Culture, Youth and Sports Office in Takalar whohad given permission to organize this program in his workingarea as well as teachers in Local Language Teacher WorkingGroup in Takalar as a forum to improve teachers‟professionalism through joint trainings. Through this activity,the results showed that local language teachers (in primary andsecondary schools) in Takalar had adequate knowledge aboutthe Curriculum 2013 (K-13), especially the BasicCompetencies and Indicators of Makassar Local LanguageLearning; the teachers are skillful in developing syllabus andlesson plan based on the K-13 with scientific approach; andthe teachers are skillful in developing teaching materials basedon learning objectives, indicators, and basic competencies thathave been formulated.